Identification of Hypoxia Induced Metabolism Associated Genes in Pulmonary Hypertension - He, Yang-Yang; Xie, Xin-Mei; Zhang, Hong-Da; Ye, Jue; Gencer, Selin; van der Vorst, Emiel P. C.; Döring, Yvonne; Weber, Christian; Pang, Xiao-Bin; Jing, Zhi-Cheng; Yan, Yi; Han, Zhi-Yan (Frontiers in Pharmacology, 2021)
Objective: Pulmonary hypertension (PH) associated with hypoxia and lung disease (Group 3) is the second most common form of PH and associated with increased morbidity and mortality. This study was aimed to identify hypoxia induced metabolism associated genes (MAGs) for better understanding of hypoxic PH. Methods: Rat pulmonary arterial smooth muscle cells (PASMCs) were isolated and cultured in normoxic or hypoxic condition for 24 h. Cells were harvested for liquid chromatography-mass spectrometry analysis. MAGs were then identified in Genecards. Transcriptomic data from lungs of hypoxic PH in mice/rats or of PH patients were accessed from GEO database or open-access online platform. Results: 36 altered metabolites and 1259 unique MAGs were identified in rat PASMCs under hypoxia. 38 differentially expressed MAGs in mouse lungs of hypoxic PH were revealed, with enrichment in multi-pathways including regulation of glucose metabolic process, which might be reversed by drugs such as blebbistatin. 5 differentially expressed MAGs were displayed in SMCs of Sugen 5416/hypoxia induced PH rats at the single cell resolution. Furthermore, 6 hub genes (Cat, Ephx1, Gpx3, Gstm4, Gstm5 and Gsto1) out of 42 unique hypoxia induced MAGs were identified. Higher Cat, Ephx1 and lower Gsto1 were displayed in mouse lungs under hypoxia (all P < 0.05), in consistent with the alteration in lungs of PH patients. The hub gene-based LASSO model can predict the occurrence of PH (AUC=0.90). Conclusions: Our findings revealed six hypoxia-induced metabolism associated hub genes, and shed some light on the molecular mechanism and therapeutic targets in hypoxic PH.